Perumusan Variabel Dan Indikator Dalam Penelitian Kuantitatif Kependidikan - Srifariyati, Srifariyati; Susianti, Oni Marliana (JURNAL PENDIDIKAN ROKANIA, 2024)
The formulation of variables is one of the important elements in a research, because a process of gathering facts or measurements can be carried out well if the research variables can be formulated firmly. This paper will discuss the definition of variables, characteristics, types of variables, and the formulation of indicators. The method used is library research. The results are 1) research variables are factors that play a role in the events or symptoms to be studied in the form of traits taken from a different values and vary. 2) In quantitative education research the characteristics of variables are measurable, distinguishing one object from another object in a population, and the value varies. Variables must be measurable, this requires research results to be objective, measurable, and always open to test. 3) Variable types include: (i) dependent variable and independent variable, (ii) moderating variable, (iii) interveining variable, (iv) intervening variable latent and manifest, (v) indogenous and exogenous variables (vi) control variables. 4) Variables will produce several research indicators, while research indicators will produce a number of items in the research questionnaire. The easiest way to determine research indicators is to list keywords from a number of theories contained in research variables. After determining the research indicators, the researcher then creates research items (list of questions) by following the arrangement of keywords or key phrases in the research indicators section.